A Comparative Study of Solid-State and Co-precipitation Methods for Synthesis of NMC622 Cathode Material from Spent Nickel Catalyst - Endah Retno Dyartanti; Tika Paramitha; Arif Jumari; Agus Purwanto; Adrian Nur; Anatta Wahyu Budiman; Shofirul Sholikhatun Nisa (Journal of Engineering and Technological Sciences, 2023)
Nickel, the main raw material for lithium-ion batteries (LIB), is currently the most in-demand metal. The rising need for nickel and current environmental concerns have underscored the importance of recycling waste metal to recover its value. Meanwhile, a significant secondary source with a high metal value is spent catalyst. In this context, the acid leaching method was used to recover nickel from spent catalyst. This study aimed to synthesize Lithium Nickel Manganese Cobalt Oxide 622 (NMC622) from spent catalyst. To determine the optimal method, a comparative analysis was conducted between solid-state and co-precipitation methods. Recycled spent nickel catalyst to be used for cathode material was examined by analytical methods, i.e., XRD, FTIR, SEM-EDX, and electrochemical performance testing. The XRD, FTIR, and SEM-EDX tests produced similar outcomes, consistent with previous reports. However, in the electrochemical test, the co-precipitation method showed a specific capacity two times higher than the solid-state method. The NMC622 from the co-precipitation method (NMC622-CP) yielded a specific discharge capacity of 132.82 mAh.g-1 at 0.1C, while the retention capacity was 70% for 50 cycles at 0.5C.